Family agriculture for inclusive rural development - Laksmi Reddiar, Krishnamurthy; Krishnamurthy, Sumithra; Rajagopal, Indumathi; Peralta Solares, Arturo (REVISTA TERRA LATINOAMERICANA, 2017)
The indigenous Mayan populations of the Yucatan peninsula of Mexico have practiced the ancient traditions of family farming, especially home gardens, to ensure their food security. With the objective of improving the traditional practice with modern science, data were collected on the structural complexity and functional diversity from 20 home gardens selected at random in each of the following five communities: X-Maben, X-Pichil, X-Yatil, San José II and Melchor Ocampo. In addition, group discussions were organized to elucidate the management strategy practiced by the indigenous people. The results show that home gardens are managed mainly by women. The main purpose of growing and maintaining home gardens is to guarantee the production of nutritious food all year round. Finally, the home gardens also serve secondary purposes such as provision of products and services for traditional medicine. This study suggests that home gardens should be promoted and invested in to improve inclusive development strategies for contexts with similar socio-cultural and biophysical circumstances.